Implementation of the Independent Curriculum in the Fiqh Subject at the Al-Khoirot Buyut Udik Lampung Islamic Senior High School - Dewi Lailatul Khusna; M. Sayyidul Abrori; Hernisawati (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2025)
This study aims to analyze the implementation of the Independent Curriculum in the Fiqh subject at Madrasah Aliyah (MA) Al-Khoirot Buyut Udik, Lampung. The Independent Curriculum provides flexibility for educators and students in choosing learning methods that are appropriate to the needs and characteristics of individuals. In the context of Fiqh learning, the implementation of this curriculum is expected to improve students' understanding and skills through a project-based approach and problem solving. This study uses a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation involving the principal, Fiqh teachers, and students of MA Al-Khoirot Buyut Udik. Data validity testing was carried out using triangulation techniques, which include source triangulation to compare information from various parties and method triangulation to ensure data consistency through various data collection techniques. Data analysis was carried out using the Miles and Huberman interactive model, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of the Independent Curriculum in Fiqh learning at MA Al-Khoirot faces several challenges, such as limited learning resources and teacher readiness in adopting more innovative learning methods. However, there are supporting factors such as high student interest in learning and curriculum flexibility that allows teachers to adjust the material to student needs. The results of this study provide implications for the development of more effective Fiqh learning strategies and can be a reference for other madrasas in implementing more adaptive curriculum policies that are oriented towards student needs.